การวิเคราะห์ความน่าเชื่อถือของระบบแบบหลายขั้นตอนกรณีที่มีการซ่อมแซม ภายใต้การแจกแจงไวบูลล์แบบฟัซซี RELIABILITY ANALYSIS FOR REPAIRABLE MULTI-STATE SYSTEM UNDER FUZZY WEIBULL DISTRIBUTION - บำรุงเศรษฐพงษ์ วิมลมาศ; ฉลองรัตนสกุล ปราโมทช์ (Srinakharinwirot University Journal of Sciences and Technology, 2021)
The purpose of this research is to present a method for analyzing the system reliability of the repairable multi-state system (RMSS) which the failure rate and repair rate are Weibull distribution with uncertain time. The vagueness coefficient with a triangular membership function is used to analyze the appropriate function of failure rate and repair rate for RMSS problems. The results showed that RMSS model had the most appropriate fuzzy system reliability when the failure rate and the repair rate of each state in the system are decreasing function under fuzzy Weibull distribution.